Special Feature: Quality Assurance, A Framework for Canadian Universities - Webster, William G. (Canadian Journal of Higher Education, 1990)
Quality assurance programs have become an integral part of the health delivery processions during the past quarter century. They generally focus on the appropriateness and adequacy of services provided, with the objective of identifying and correcting deficiencies of service. Appropriateness and adequacy are assessed by the degree of adherence of practices to explicit standards, and these in turn relate to criteria of structure, process, outcome and efficiency. The key concepts and methodologies of quality assurance programs are reviewed, and it is suggested that they can be readily applied to Canadian universities. A quality assurance program within a university could be a powerful administrative and curricular development tool that would serve to define and enhance the quality of educational experiences of students.